2014
DOI: 10.1200/jco.2013.54.5947
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Vitamin D Concentration Influences Survival Outcome After a Diagnosis of Colorectal Cancer

Abstract: Purpose We investigated whether the plasma level of 25-hydroxyvitamin D (25-OHD) after a diagnosis of colorectal cancer (CRC) influences survival outcome. Patients and Methods We prospectively studied 1,598 patients with stage I to III CRC. We sought association between plasma 25-OHD and stage-specific survival and tested for interaction between 25-OHD level and variation at the vitamin D receptor (VDR) gene locus. Blood was sampled postoperatively, and plasma was assayed for 25-OHD by liquid chromatography-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(149 citation statements)
references
References 39 publications
(10 reference statements)
5
137
4
3
Order By: Relevance
“…The findings from the meta-analysis provide strong epidemiological evidence for the important role of vitamin D in bladder carcinogenesis. There are several studies published to assess the role of vitamin D deficiency on the prognosis of cancer patients, and vitamin D deficiency may decrease the overall survival of cancer patients, such as colorectal cancer [28]. However, there is no study performed to assess the relation of vitamin D deficiency with prognosis of bladder carcinoma patients, and there is still lack of clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from the meta-analysis provide strong epidemiological evidence for the important role of vitamin D in bladder carcinogenesis. There are several studies published to assess the role of vitamin D deficiency on the prognosis of cancer patients, and vitamin D deficiency may decrease the overall survival of cancer patients, such as colorectal cancer [28]. However, there is no study performed to assess the relation of vitamin D deficiency with prognosis of bladder carcinoma patients, and there is still lack of clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…A U-shaped relationship was observed for prediagnostic 25(OH)D and breast cancer mortality in the Swedish Malmo cohort (81). On the basis of blood samples taken after diagnosis, a higher level of 25(OH)D was associated with a lower colorectal cancer mortality (82,83), ovarian cancer mortality (84), and Merkel cell carcinoma mortality (although not significant) (85). Higher postdiagnostic 25(OH)D status was also associated with significantly improved pancreatic cancer survival in 1 study (86).…”
Section: Or In the European Prospective Investigation Into Cancer Andmentioning
confidence: 98%
“…Both meta-analyses showed that patients with colorectal cancer with high vitamin D levels compared with patients with low vitamin D levels had a significantly reduced overall and colorectal cancer-specific mortality (4,5). One recent additional study that focused on postoperative vitamin D levels also showed that vitamin D status was inversely associated with both overall and colorectal cancer-specific mortality (9). Table 1 provides details of all published prospective studies on vitamin D status and colorectal cancer survival.…”
Section: Introductionmentioning
confidence: 99%